Communicating Identity in the Workplace and Affinity Groups Spaces - (:unkn) unknown (My University, 2016)
The following dissertation examined affinity group creation and purpose. By using identity management theory and communication privacy management theory the author was able to understand what one both reveals and conceals within an affinity group and organization at large. Two studies addressed the utility of an affinity group for those currently involved in homogeneous racial and nonracial groups, as well as for future employees who may become the next affinity group attendees. Using a thematic analysis, Study I revealed affinity group perceptions including several subthemes (logistics, helpful, harmful, more heterogeneity, and exclusion of identity). Organizational diversity sessions at large revealed similar subthemes (legitimizing identity, lack of safe spaces, intersectionality, and surface level discussions). Using a qualitative content analysis, Study II revealed that racial and nonracial minorities found affinity groups beneficial, whereas all opposed identified as White. Additionally, varied results found for what one discusses within an affinity group space, including open to discussing anything, as well as closed to providing any personal information. Participants also reported socially appropriate workplace topics including surface level topics, whereas inappropriate topics included religion, politics, and race. Understanding how future employees see diversity in an organizational context will better equip organizations to enact specific diversity strategies that move beyond the mere rhetoric of diversity.
Keywords: Affinity Groups; Diversity; Identity; Intersectionality; Privacy Management; Privilege